PENERAPAN METODE SMALL GROUP DISCUSSION (SGD) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Muthia Dewi; Sri Rezki Maulina Azmi; Dailami Dailami; Anita Purba (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: The aim of this research is to find out how the Small Group Discussion learning process is implemented in students' critical thinking abilities. This type of research is Classroom Action Research. Where operations in this research are described into four stages in the form of a cycle, namely the planning, action, observation and reflection stages. The subjects in this research were STMIK Royal Kisaran students and the object in this research was students' critical thinking skills using the Small Group Discussion method. The research instruments for collecting data were initial tests, learning outcomes tests, interviews and observations. Based on the research results, the total score obtained from the implementation of learning in cycle 1 in class was categorized as less successful with an average score of 2.5. The total score obtained in cycle 2 was categorized as less successful with an average score of 2.88. The total score obtained from the implementation of learning in cycle 3 was categorized as successful with an average score of 3.75. Thus, in cycle 3 the implementation of learning was categorized as successful.Keywords: small group discussion; critical thinking abilities Abstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana penerapan proses pembelajaran Small Group Discussion dalam kemampuan berpikir kritis mahasiswa. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Dimana operasional dalam penelitian ini dijabarkan menjadi empat tahap yang berupa siklus yaitu tahap perencanaan, tindakan, observasi dan refleksi. Subjek dalam penelitian ini adalah mahasiswa STMIK Royal Kisaran dan objek dalam penelitian ini kemampuan berpikir kritis mahasiswa menggunakan metode Small Group Discussion. Instrumen penelitian dalam mengumpulkan data adalah tes awal, tes hasil belajar, wawancara dan observasi. Berdasarkan hasil penelitian diperoleh Jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 1 di kelas dikategorikan kurang berhasil dengan rata-rata skor 2,5. Jumlah skor yang diperoleh pada siklus 2 dikategorikan kurang berhasil dengan rata-rata skor 2,88. Jumlah skor yang diperoleh dari pelaksanaan Pembelajaran pada siklus 3 dikategorikan berhasil dengan rata-rata skor 3,75. Dengan demikian pada siklus 3 pelaksanaan pembelajaran dikategorikan berhasil.Kata kunci: small group discussion; kemampuan berpikir kritis